Backcup Router Network Optimization to Prevent Link Failure Using the Virtual Router Redundancy Protocol (VRRP) Method: Backcup Router Network Optimization to Prevent Link Failure Using the Virtual Router Redundancy Protocol (VRRP) Method - Adjie Santoso; Moh. Iwan Wahyuddin; Andri Aningsih (Institute of Computer Science (IOCS), 2020)
The internet network runs without stopping as its usage increases, if the Router experiences a problem of downtime then the internet cannot be used. To minimize these problems, the Backcup Router can be applied using the VRRP method. Testing in this study will use packet loss and throughput parameters. From the results of tests that have been done show that the application of the VRRP method can provide optimal network availability by providing a Router Backcup and produces an average packet loss value of 0.39%, and an average throughput of 279 Bps is said to be very good, with the results of applying the method VRRP is able to provide solutions when the main router is experiencing problems and still maintaining the quality of the internet network.